Accident investigations in the merchant marine - Švetak, Jelenko (Array, 2007)
A survey of total loss accidents in the merchant marine over a period of 30 years has shown that these accidents can be arranged in the following order: stranding, fire, water-leaks, gales and collision; other accidents have also been taken into consideration. The analysis covers ships over 500 GT flying different flags and plying any route of navigation. At the beginning, a sample of 500 merchant ships - of different types and tonnage - and flying 15 different flags has been analyzed to determine the age and type of ship, as well as the causes of accidents. In the second analysis, the same ships flying 15 flags are considered, but now over a wider range and on a sample totaling 1,500 merchant ships. The results of both the analyses have been compared. It resulted that all collisions, together with gales, amount to 25% of the maritime casualty returns -in the total loss lists- while stranding and collision take more than 40% of the toll